Pengembangan Media Pembelajaran Mobile Learning Berbasis Android Pada Materi Barisan dan Deret Aritmatika Kelas VIII SMPN 07 Putussibau - Karpina Sapitri; Rahman Haryadi; Hartono Hartono (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2024)
This research aims to produce Android-based mobile learning learning media on sequence and arithmetic series material for class VIII SMPN 07 Putussibau. This research uses the ADDIE development design model, which consists of five main stages, namely analysis, design, development, implementation and evaluation. The subjects in this research were class VIII students at SMP Negeri 07 Putussibau. The instruments used in this research were validation sheets, questionnaires and tests in the form of essay questions. The results of the research showed that the validity of the Android-based mobile learning learning media on arithmetic sequences and series material was categorized as very valid, the practicality of the Android-based mobile learning learning media on the arithmetic sequences and series material was categorized as very practical, and the Android-based mobile learning learning media on the sequence and series material. arithmetic is categorized as effective.